Kidney decellularized extracellular matrix hydrogels: Rheological characterization and human glomerular endothelial cell response to encapsulation. Issue 9 (25th September 2018) - Su, Jimmy; Satchell, Simon C.; Shah, Ramille N.; Wertheim, Jason A.
Abstract: Hydrogels, highly‐hydrated crosslinked polymer networks, closely mimic the microenvironment of native extracellular matrix (ECM) and thus present as ideal platforms for three‐dimensional cell culture. Hydrogels derived from tissue‐ and organ‐specific decellularized ECM (dECM) may retain bioactive signaling cues from the native tissue or organ that could in turn modulate cell–material interactions and response. In this study, we demonstrate that porcine kidney dECM can be processed to form hydrogels suitable for cell culture and encapsulation studies. Scanning electron micrographs of hydrogels demonstrated a fibrous ultrastructure with interconnected pores, and rheological analysis revealed rapid gelation times with shear moduli dependent upon the protein concentration of the hydrogels. Conditionally‐immortalized human glomerular endothelial cells (GEnCs) cultured on top of or encapsulated within hydrogels exhibited high cell viability and proliferation over a one‐week culture period. However, gene expression analysis of GEnCs encapsulated within kidney dECM hydrogels revealed significantly lower expression of several relevant genes of interest compared to those encapsulated within hydrogels composed of only purified collagen I. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A:2448–2462, 2018.